2017
DOI: 10.1111/ejn.13504
|View full text |Cite
|
Sign up to set email alerts
|

In vitro differentiation of neural stem cells derived from human olfactory bulb into dopaminergic‐like neurons

Abstract: This study describes a new accessible source of neuronal stem cells that can be used in Parkinson's disease cell transplant. The human olfactory bulb contains neural stem cells (NSCs) that are responsible for neurogenesis in the brain and the replacement of damaged cellular components throughout life. NSCs are capable of differentiating into neuronal and glial cells. We isolated NSCs from the olfactory bulb of brain-death donors and differentiated them into dopaminergic neurons. The olfactory bulb tissues obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…Among these 4 genes, SOX2 showed the highest significant up-regulation level. In consistent with our findings, a previous study reported early activation of SOX2 in NSCs derived from adult human OB (Alizadeh et al, 2017) and in the embryonic nervous system, predominantly in the proliferating, undifferentiated precursors (Pevny and Nicolis, 2010). Unlike SOX2, MSI1 gene, which is a marker for neuronal progenitor cells (Uren et al, 2015), showed the lowest expression level.…”
Section: Discussionsupporting
confidence: 93%
“…Among these 4 genes, SOX2 showed the highest significant up-regulation level. In consistent with our findings, a previous study reported early activation of SOX2 in NSCs derived from adult human OB (Alizadeh et al, 2017) and in the embryonic nervous system, predominantly in the proliferating, undifferentiated precursors (Pevny and Nicolis, 2010). Unlike SOX2, MSI1 gene, which is a marker for neuronal progenitor cells (Uren et al, 2015), showed the lowest expression level.…”
Section: Discussionsupporting
confidence: 93%
“…Cell transplantation has been emerged as a promising therapeutic approach to treat a variety of neurological disorders [54]. Among the candidate cells for cell therapy, OE-MSCs are derived easily from olfactory mucosa due to their unique properties such as high proliferation rate and meso-ectodermal origin.…”
Section: Identification Of Mscs Derived From Nasal Mocusamentioning
confidence: 99%
“…These characteristics predispose them to become an applicable cell source in cell therapy for neurodegenerative diseases (Alizadeh et al, 2017, Chun et al, 2016. In vitro differentiation of oligodendrocytes from hDPSCs depends on various differentiation procedures with different inducers.…”
Section: Discussionmentioning
confidence: 99%